Transdermal absorption enhancement of rice bran bioactive compounds entrapped in niosomes - Manosroi A. (2014)
Niosomes composed of Tween 61 and cholesterol at 1:1 molar ratio were entrapped with the mixture of the three semi-purified rice (Oryza sativa L., Family Gramineae) bran bioactive compounds [ferulic acid (F), γ-oryzanol (O), and phytic acid (P)] at 0.5%, 1.5%, and 1.5%, respectively, by the supercritical CO 2 technique. The transdermal absorption by vertical Franz diffusion cells of the compounds entrapped in niosomes (Nio FOP), the unentrapped compounds (Mixed FOP), the compounds incorporated in gel and cream (Gel FOP and Cream FOP), and the compounds entrapped in niosomes and incorporated in gel and cream (Gel nio and Cream nio) was investigated. At 6 h, F and P from Nio FOP gave lower cumulative amount in viable epidermis and dermis (VED) than from Mixed FOP of 1.1 and 1.6 times, respectively, while O from Nio FOP exhibited higher cumulative amount in VED than from Mixed FOP of 2.4 times. The highest cumulative amount in VED of F, O, and P were from Gel nio, Cream nio, and Mixed FOP at 1.564±0.052, 15.972±0.273, and 25.857±0.025 ng/cm 2, respectively. Niosomes enhanced the transdermal absorption of the hydrophobic compound O, while retarded the hydrophilic compounds F and P indicating the less systemic risk of F and P than O when entrapped in niosomes. Thus, transdermal absorption of F, O, and P appeared to depend on niosomal size, lipophilicity of the bioactive compounds, and types of formulations. These preclinical results can be applied for the design of the clinical study of the developed rice bran niosomal topical products. © 2012 American Association of Pharmaceutical Scientists.